(untitled) (International Journal of Psychiatric Nursing, 2025)
Background: Children often suffer from various stressors and strains, and parents and teachers must know about the complexity of their kids. It is also the responsibility of parents and teachers to provide them with a completely healthy environment that is psychologically satisfying and socially acceptable. The mean post-test attitude scores of primary school teachers on early detection and management of behavioural and emotional problems of children will be significantly higher in the post-test of the experimental group than those of the control group as measured by the Attitude of Teachers towards Students with Behavioral problems (ATSB scale). Objective: The study was conducted to assess the effectiveness of the Structured Teaching Module in changing the attitude of primary school teachers towards early detection and management of behavioural and emotional problems in students. Materials and methods: A quantitative evaluative research approach was employed with a true experimental, pre-, and post-test research design. The sample consisted of 50 teachers in the experimental and control groups (n=100), selected using a simple random sampling technique. Results: In the experimental group, the mean attitude scores of post-test two (A3) 169.62± 15.8, post-test one (A2) 148.78±18.432 were significantly higher than the pre-test (A1) mean knowledge score 83.76±4.47. In the control group attitude scores of post-test two (A3)83.53±6.24, post-test one (A2) 83.60±5.167 was higher than the pre-test mean score (A1) 83.6±5.17. There was an increase in the mean attitude scores in the experimental group (85.86%). In the control group also there was an increase (0.07%), which was minimal. The difference in mean percentage of the experimental and the control group is 40.04%. Conclusion: The Structured Teaching Module was effective in developing a positive attitude toward the behavioural and emotional problems of primary school students among teachers.